2018
DOI: 10.1016/j.jid.2017.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte Sonic Hedgehog Upregulation Drives the Development of Giant Congenital Nevi via Paracrine Endothelin-1 Secretion

Abstract: Giant congenital nevi are associated with clinical complications such as neurocutaneous melanosis and melanoma. Virtually nothing is known about why some individuals develop these lesions. We previously identified the sonic hedgehog (Shh) pathway regulator Cdon as a candidate nevus modifier gene. Here we validate this by studying Cdon knockout mice, and go on to establishing the mechanism by which Shh exacerbates nevogenesis. Cdon knockout mice develop blue nevi without the need for somatic melanocyte oncogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Some of these have been shown to influence melanocytes via the increased production of keratinocyte cytokines (Table 1 and Figure 1d). For instance, perturbation of Ptch1 and Smo leads to increased Edn1 secretion in mice, whereas loss of Nfib leads to Edn2 up-regulation (Chang et al, 2013;Chitsazan et al, 2018). Inactivating mutations in ribosomal subunit genes leads to hyperpigmentation (McGowan et al, 2008;Terzian et al, 2011) via increased in Kitl expression and secretion from keratinocytes (Table 1).…”
Section: Genes and Pathways Influencing Melanocyte Number In Micementioning
confidence: 99%
See 1 more Smart Citation
“…Some of these have been shown to influence melanocytes via the increased production of keratinocyte cytokines (Table 1 and Figure 1d). For instance, perturbation of Ptch1 and Smo leads to increased Edn1 secretion in mice, whereas loss of Nfib leads to Edn2 up-regulation (Chang et al, 2013;Chitsazan et al, 2018). Inactivating mutations in ribosomal subunit genes leads to hyperpigmentation (McGowan et al, 2008;Terzian et al, 2011) via increased in Kitl expression and secretion from keratinocytes (Table 1).…”
Section: Genes and Pathways Influencing Melanocyte Number In Micementioning
confidence: 99%
“…Using a screen tool to detect natural genetic variation that modifies the density and histopathology of melanocytic nevi developing in a melanoma-prone mouse model, we found that nevus development was exacerbated in a cellextrinsic manner by keratinocytes. It involves up-regulation of Shh signaling and its downstream targets such as Gli transcription factors in keratinocytes and their subsequent secretion of the melanocyte mitogen Edn1 (Chitsazan et al, 2016(Chitsazan et al, , 2018. It is well known that nevi mostly carry cell intrinsic oncogenic mutations (e.g., BRAF, NRAS, GNAQ) that stimulate the MAPK pathway, but little is known about germline factors playing a role in nevus growth.…”
Section: Introductionmentioning
confidence: 99%
“…These mutations affect the microtubule-associated protein kinase (MAPK) signal transduction pathway, leading to abnormal proliferation of embryonic melanoblasts [ 1 ]. Recent evidence suggests that Cdon, a regulator acting via the sonic hedgehog pathway, exacerbates the development of CMN in the context of an NRAS mutation by causing excessive release of endothelin-1 [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical studies to substantiate this claim are yet to be conducted. Use of endothelin-1 receptor antagonists has been proposed as a therapeutic approach for GCMN, based on evidence generated from preclinical studies [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inbred CC mice used in combination with other mouse models (e.g., transgenic) have also been applied, for example, in the identification of a mutation in the Cdon gene that accelerates congenital navus growth (Chitsazan et al, 2016). The function of this gene has now been further investigated using knockout mouse models (Chitsazan et al, 2017). Simulations of the power and precision of genetic mapping with the CC population demonstrated superior performance relative to traditional or alternative strategies (Broman, 2005; Valdar et al, 2006; Ram et al, 2014; Ram and Morahan, 2017).…”
Section: Approaches To Identify the Genetic Architecture Of Osteoporosismentioning
confidence: 99%